Understanding Savings Behavior: A New Savings Typology Based on Individual Voluntary Savings Accounts - Amin, Ashirul. (2017)
Abstract: Mass-market retail banks targeting low-income individuals offer no-frills voluntary accounts to make banking services accessible to the unbanked or underbanked. The granular transaction and balance information collected for each client is a treasure trove of behavioral data, yet a lack of analytical frameworks, computational power and motivation makes them difficult to analyze. To enable us to delve into such large datasets better, this thesis develops a savings typology discovery methodology that relies on finding patterns in episodic periods of savings (or "segments"). It harmonizes each segment to make them comparable to each other, uses k-median cluster analysis to bucket similar patterns, and classifies recurring behavioral savings patterns, or "motifs," into five groups: Accumulators, Sustained Balances, Fast Drawdown, Slow Drawdown, and Dump-and-Pull. The Dump-and-Pull motif involves a short-term, pass-through mechanism that is not savings oriented. Accumulators are accretive savers who demonstrate that discipline-intensive behaviors are possible using bank accounts. The other three represent different levels of initial cashflow intermediation. Together, they show that the use of no-frills savings accounts do seem to further the cause of financial inclusion by accommodating a wide variety of behavior, savings and otherwise. We evaluate the efficacy of motifs by exploring the additional explanatory capacity they provide in understanding banking agent usage, deployment of which occurred during the period covered in the dataset. We utilize Arellano-Bond GMM Estimators to explore the relationship between agents, motifs and outcome variables, with a special interest in the interaction between agent usage and motifs. We find that Accumulators and Sustained Balance motifs show increased interaction in smaller amounts, Fast and Slow Drawdowns have more lumpy interactions, and Dump-and-Pull show an overall decrease in involvement. The primary association with agents is through changes in the number of deposits, and then, by how much is withdrawn.; Thesis (Ph.D.)--Tufts University, 2015.; Submitted to the Dept. of Economics and International Business.; Advisor: Jenny Aker.; Committee: Carolyn Gideon, Kim Wilson, and Daryl Collins.; Keyword: International relations.